Ebu'd-Derdâ'nın hayatı ve rivayetleri - Sevim, Sena (Fatih Sultan Mehmet Vakıf Üniversitesi, 2025)
Ashâb, İslâm'ın ilk döneminden itibaren Rasûlullah'ın (s.a.) yanında yer almış; vahye muhatap olmuş ve İslâm'ın evrensel mesajlarını diğer insanlara ulaştırmak amacıyla büyük bir çaba sarf etmiştir. İlmi, ahlâkı ve hikmetli nasihatleriyle tanınan Ebû'd-Derdâ, ashâb içerisinde müstesna bir konuma sahiptir. Rasûlullah'ın (s.a.) takdirine mazhar olan bu sahâbînin hayatı ve rivâyetleri, İslâm tarihi ve hadis ilmi açısından önem arz etmektedir. Bu çalışmada, Ebû'd-Derdâ'nın hayatı; takvâ anlayışı, ibadete olan bağlılığı, İslâm'ı öğretme amacıyla yürüttüğü eğitim faaliyetleri kapsamlı bir biçimde ele alınmış; özellikle hadis ve sünnet alanındaki yeri tespit edilmeye çalışılmıştır. Bu sayede, adı geçen sahâbînin ilmî ve ahlâkî yönleriyle daha iyi anlaşılması hedeflenmiştir. Çalışmanın devamında, Ebû'd-Derdâ'nın Rasûlullah'tan (s.a.) rivâyet ettiği itikâd, ibâdet, ahlâk ve muâmelâta dair hadisler tahlil edilmiş; bu rivâyetlerden çıkarılan sonuçlara yer verilmiştir.

The Companions (al-Sahabah) stood by the Messenger of Allah (peace be upon him) from the earliest period of Islam. They were directly addressed by divine revelation and made great efforts to convey Islam's universal message to others. Among them, Abu Derda held a distinguished position, known for his knowledge, moral character, and wise counsel. This Companion, who was praised by the Prophet (peace be upon him), holds a significant place in Islamic history and the science of hadith due to his life and narrations. This study offers a comprehensive examination of Abu Darda's life, focusing on his understanding of piety, devotion to worship, educational efforts aimed at teaching Islam. In particular, the research attempts to identify his role and status in the field of hadith and the Sunnah. In doing so, it seeks to provide a better understanding of his intellectual and ethical qualities. In the subsequent sections, the study analyzes the hadiths he transmitted from the Prophet (peace be upon him) related to creed ('aqidah), worship ('ibadah), ethics (akhaq), and social conduct (mu'amalat), and presents the conclusions drawn from these narrations.
The life of Abu'l-Darda and his narrations
Keywords: Din; Religion